The Mjølnir impact event and its consequences geology and geophysics of a late jurassic/early cretaceous marine impact event - Dypvik, Henning; Tsikalas, Filippos; Smelror, Morten (Impact studies., 2010)
The Mjølnir impact structure was recognized in 1993 and included in the Earth Impact Database in 1996, based on the discoveries of unequivocal meteorite impact indicators such as shocked quartz, Ir-enrichments, possible glass remnants, fragments of nickel-rich iron oxides, in addition to the convincing complex crater shape of the structure. This book presents the geological and geophysical history of the Barents Sea region along with the discovery of the Mjølnir impact crater. We place the Mjølnir event into the geological framework of the region and present elaborative numerical models of its formation and associated tsunami generation. The book represents an update and synthesis as well as the complete compilation of the Mjølnir crater stu